2011
DOI: 10.1109/tvt.2010.2089545
|View full text |Cite
|
Sign up to set email alerts
|

Channel Modeling of Information Transmission Over Cognitive Interrogator-Sensor Networks

Abstract: Abstract-This paper looks into the modeling of information transmission over cognitive interrogator-sensor networks (CISNs), which represent a novel and important class of sensor networks deployed for surveillance, tracking, and imaging applications. The crux of the problem is to develop a channel model that allows for the evaluation of the sensing channel capacity and error rate performance in CISNs, for which the sensing link is overlaid by the communication link. First, the layered discrete memoryless chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…As the CR concept matures, CR networks are now envisioned to support a variety of applications, ranging from the smart grid, public safety and broadband cellular, and medical applications to wireless sensor networks (WSNs) [11,[57][58][59]. For instance, in the aerospace industry, major aircraft manufacturers and many supply research groups have shown strong interest in development and standardization of sensor networks for onboard use within aircraft, e.g., the "Wireless Avionics Intra-Communications (WAIC)" project by the Aerospace Vehicle System Institute.…”
Section: Motivationsmentioning
confidence: 99%
“…As the CR concept matures, CR networks are now envisioned to support a variety of applications, ranging from the smart grid, public safety and broadband cellular, and medical applications to wireless sensor networks (WSNs) [11,[57][58][59]. For instance, in the aerospace industry, major aircraft manufacturers and many supply research groups have shown strong interest in development and standardization of sensor networks for onboard use within aircraft, e.g., the "Wireless Avionics Intra-Communications (WAIC)" project by the Aerospace Vehicle System Institute.…”
Section: Motivationsmentioning
confidence: 99%
“…Therefore, the information in the CRSN can be efficiently and reliably transmitted in the unutilized licensed spectrum. Recently, CRSN has attracted much research attention [13,14,15,16,17,18,19]. An optimal schedule scheme for a sensor-aided energy-efficient cooperative network was designed in [13].…”
Section: Introductionmentioning
confidence: 99%
“…In [16], the authors analyzed the delay performance and designed two channel switch methods for CRSN. The work [17] investigated the modeling methods for information transmission, and [18] analyzed the spectrum efficiency through a graph-theoretic max-flow framework for CRSN. Spectrum and power allocation and routing were jointly considered to maximize the information rate, as well as the lifetime of CRSN [19].…”
Section: Introductionmentioning
confidence: 99%
“…Second, a CSN does not require high bandwidth or high data rate communication links in general, similar to wireless sensor networks (WSNs) [4]. As the CR concept matures, CSNs are now envisioned to support a variety of applications, ranging from smart grid, public safety and broadband cellular, and medical applications to WSNs [4][5][6][7][8][9]. For instance, in the aerospace industry, major aircraft manufacturers and many supply research groups have shown strong interest in development and standardisation of sensor networks for onboard use within aircraft where different applications have various design requirements.…”
Section: Introductionmentioning
confidence: 99%